Forest Governance in Nepal: Rationale for Centralised Forest and Wildfire Management - Somlai, Iván Győző; Karakatsoulis, John; Gardner, Wendy; Gautam, Ambika P.; Sharma, Sundar Prasad; Adhikari, Bharat (Journal of Management and Development Studies, 2018)
Numerous inter-related social and institutional factors are causing concern as to effective responses to the increasing number and severity of forest and wildfires in Nepal, due in similar measure to socio-cultural, politico-bureaucratic as well as global climatic issues. Our binational team of multisectoral field practitioners in bureaucratic as well as natural resource and fire management compiled and verified background information to more clearly discern the issues affecting improved fire governance and thereupon has made supportive recommendations for the belated establishment of a dedicated unit within the Government of Nepal Ministry of Forests and Soil Conservation to coordinate, administer and manage a comprehensive forest fire management programme.